Strategi Negosiasi dalam Manajemen Konflik Organisasi - Kasirul Fadli; Shabrina; Nurcahyani; Zuraini (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study aims to determine that conflict in an organization is an unavoidable phenomenon due to differences in interests, goals, and perceptions among members. Proper conflict management is the key to maintaining work effectiveness and stability in an organization. This study aims to identify various types of conflicts that often occur in organizations and to examine effective negotiation strategies in managing these conflicts. Using the literature study method, this study analyzes various academic sources and practices related to negotiation in the context of organizational conflict management. The results of the study indicate that understanding the root causes of conflict, implementing appropriate negotiation strategies, and managing success factors such as cooperation, compromise, avoidance, competition, and adaptation play an important role in achieving mutually beneficial agreements. However, this study also reveals various obstacles that often arise in the negotiation process, such as individual ego, unclear goals, and power imbalances between conflicting parties. The implications of this study provide guidance for managers to optimize negotiation strategies to create more effective conflict resolution.